Novel moisture management test of polyethylene terephthalate and nylon fabric under stretching and surface patterning - Huang, Jingfeng (2019)
This report presents a novel technique to assess the moisture management test on uniformly stretched compression fabrics using a clamping device, which represents behavior close to the actual behavior when worn, the effects of stretching on hydrophobic/hydrophilic and surface patterning on polyethylene terephthalate (PET) and nylon fabrics. The wicking behaviors of stretching, coating and patterning are discussed. We report that (1) coated compression fabrics were found to enhance moisture management based on the bottom spreading speed, top absorption rate and one-way transport capability criteria, (2) stretching plays a significant role in moisture management and (3) the best moisture management performance was exhibited by the hydrophobic inner and hydrophilic outer-coated PET fabric, under stretched conditions.